Cyanobacteria-based bioprocess for cosmetic products—cyanobium sp. as a novel source of bioactive pigments - Pagels, Fernando (2023)
As a producer of pigments with known bioactive potential, cyanobacteria are a great source of active ingredients for cosmetics (i.e., carotenoids and phycobiliproteins). Multiple phases in the cyanobacteria-based bioprocess led to the obtention of these compounds. The marine Cyanobium sp. LEGE 06113 has been proposed as a promising source for pigments for cosmetic uses, and it has been optimized in the past few years in terms of production, extraction, and application of pigment extracts. This report aims at providing an overview of the cyanobacteria-based bioprocess, regarding optimization strategies, consolidating into a proposed bioprocess for this cyanobacterium. The optimization of Cyanobium sp. included strategies regarding its production (culture medium, light, temperature, pH and salinity) and extraction (successive solvent extraction and ohmic heating). After the optimization, the two pigment-rich extracts (carotenoids and phycobiliproteins) were assessed in terms of their cosmetic potential and compatibility as an ingredient. Finally, aiming a scale-up proposal, life cycle assessment (LCA) was used as tool for a sustainable process. Ultimately, the proposed process gives the possibility to obtain two stable cosmetic ingredients from the same biomass and applied as anti-agent agents, especially due to their high anti-hyaluronidase capacity. Moreover, there remain challenges and information regarding novel cosmetic ingredient regulations were also discussed.